606 Incidence & Influence of Drug Screening in Children with Hypersomnolence During MSLT: Analysis of the Children's Wisconsin Cohort. (3rd May 2021) - D'Andrea, Lynn; Handa, Arun; Amos, Louella; Bandla, Hariprasad; Castner, Lauren; Grekowicz, Megan; Graf, Danielle; Kump, Theresa; Pan, Amy; Barbeau, Jody
Abstract: Introduction: The Multiple Sleep Latency Test (MSLT) is a validated test for evaluation of hypersomnolence in children and adults. AASM practice parameters recommend performing urine drug screens (UDS) in patients undergoing MSLT to identify substances that alter MSLT results. The study aims are to determine the incidence of positive UDS and their influence on MSLT variables in a cohort of children evaluated for hypersomnolence. Methods: All children undergoing an MSLT in Children's Wisconsin sleep laboratory over an 8-year period (11/1/2012 to 9/30/2020) were included in this retrospective chart review study. Clinical and demographic data, including UDS results were manually abstracted. Record validation conducted by random allocation. Data were summarized as median and IQR or n (%). Chi-square test or Fisher's exact test were used to examine associations between categorical variables. Results: 236 children completed an MSLT. The sample had a median age of 14.1 (IQR 10.5–16.2) years (50.9% female; 63.1% Caucasian). Narcolepsy I ("N1"; n=14; 5.9%), Narcolepsy II ("N2"; n=56; 23.7%), Idiopathic Hypersomnia ("IH"; n=39; 16.5%) were frequently diagnosed. Most children (97.9%) completed a UDS; 60.2% tested positive. Common substances found on UDS were caffeine (62.6%), OTC medications (40.3%), and prescription medications (33.8%), however nicotine (14.3%) and cannabis (5.8%) were also seen. Caffeine was commonly found in those diagnosed with N1 (70%), N2 (69.4%), and IH (54.2%). Fewer children diagnosed with narcolepsy were positive for prescription medications compared to those diagnosed with IH (21.7% versus 41.7%) although results did not reach significance (p=0.08). No child with N1 tested positive for prescription medications. ≥2 substances were found in 43.2% of positive drug screens. OTC medications and caffeine were most commonly co-occurring (23%); OTC analgesics being the most common OTC medication. No association between positivity for >2 substances and sleep diagnosis was found (p=0.5). Conclusion: More than half of children undergoing an MSLT had a positive UDS for >1 substance. The impact of these substances on PSG/MSLT parameters (total sleep time, mean sleep onset latency, sleep onset REM periods) is under investigation through additional analysis. Based on the above data our findings support the AASM guidelines of children obtaining a UDS on the day of MSLT. Support (if any):